Advances in Lead-Free Piezoelectric Materials - Wu, Jiagang (Springer Singapore, 2018)
This book systematically reviews the history of lead-free piezoelectric materials, including the latest research. It also addresses a number of important issues, such as new types of materials prepared in a multitude of sizes, structural and physical properties, and potential applications for high-performance devices. Further, it examines in detail the state of the art in lead-free piezoelectric materials, focusing on the pathways to modify different structures and achieve enhanced physical properties and new functional behavior. Lastly, it discusses the prospects for potential future developments in lead-free piezoelectric materials across disciplines and for multifunctional applications. Given its breadth of coverage, the book offers a comprehensive resource for graduate students, academic researchers, development scientists, materials producers, device designers and applications engineers who are working on or are interested in advanced lead-free piezoelectric materials.